Factors and Concequences of Dementia Among Adults of Old Age in Karachi - Fareeha Shahid, Sabahat Tahir, Ahmad Hassan, Laiba Sana, Maha Arshud, Suleman Yasin, Sundus Siddique, Aseef Ullah, Hibbah Nadeem, (Pakistan Journal of Medical & Health Sciences, 2023)
Dementia is one to the leading cause of mental impairment with 57.4 million individuals globally in 2019. This number is expected to increase up to 83.2 million by 2030 and 116 million by 2050(1). In Pakistan however, an estimated 150,000–200,000 patients are living with dementia(2). This study aims to find out the severity of dementia in patients and how this severity affects the quality of life of caretakers of dementia patients. Along with this study also aims to find out the factors involved in causing dementia. Methodology: To find the association between dementia and quality of life, a cross sectionals. Study was conducted by through a questionnaire having CDR® scale (to find severity of dementia), Zarit Burden Interview (to assess burden on caregivers) and factors leading to dementia by targeting caregivers of dementia patients in different parts of Karachi. According to the sample size 383 responses were collected. Data was than analyzed by using SPSS version 27 using crosstabs, regression. Results: Study revealed that dementia is associated with impaired life style of a care giver. ANOVA and regression was applied. Results of Regression analysis which showed that dementia does cause impaired lifestyle of caregiver as p value was 0.01(< 0.05). Different factors were assessed to find out if they lead to dementia or not. Among all only family history. Conclusion: This study showed that quality of life of caregiver was affected by taking care of dementia patients and takes a huge toll on them, financially and mentally both. Both genders from different socioeconomic backgrounds were included in the study. Most of the participants were mild to moderately affected. Results implicate that most common factors, according to the caregiver that lead to dementia were family history and unhealthy eating habits. There were other rare factors that also came up during the data collection such as head injury. Keywords: Dementia, Aging, QOL, Quality of life.